Teo-logika rzeczywistości. Stwórczy Logos a „autonomia rzeczy ziemskich” w interpretacji Josepha Ratzingera–Benedykta XVI - SZYMIK, Jerzy (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
Joseph Ratzinger/Benedict XVI treats the words from the Prologue of the Gospel of John: “In the beginning was the Word (Logos)” as the fundamental principle of the entire reality, one that determines the essential, ontic rationality/ meaningfulness of the universe because it points to its beginning – the Creator. Meaning is not a result but the principle of existence or action – by virtue of creation itself, and Christology makes us aware that meaning is, in essence, identical with love and, consequently, accessible in history and cognizable to man (incarnated). Maintaining this «logic of the Logos» protects Christian faith from mythicality, violence, autosoterism, and moralism. Only humble acceptance of the gift and kenotic unification with Christ – the eternal Logos – in prayer allows man to recognize the true meaning of the world.